2010
DOI: 10.3109/07420528.2010.515324
|View full text |Cite
|
Sign up to set email alerts
|

PROXISOME PROLIFERATOR-ACTIVATED RECEPTOR-α MEDIATES HIGH-FAT, DIET-ENHANCED DAILY OSCILLATION OF PLASMINOGEN ACTIVATOR INHIBITOR-1 ACTIVITY IN MICE

Abstract: Acute thrombotic events frequently occur in the early morning among hyperlipidemic patients. The activity of plasminogen activator inhibitor-1 (PAI-1), a potent inhibitor of the fibrinolytic system, oscillates daily, and this is considered one mechanism that underlies the morning onset of acute thrombotic events in hyperlipidemia. Although several studies have reported the expression of the PAI-1 gene is under the control of the circadian clock system, the molecular mechanism of the circadian transactivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…ARNTL2 may functionally replace ARNTL, and PER2 preferentially inhibits ARNTL2:CLOCK heterodimer activity, emphasizing its negative role and a positive role of ARNTL2 in the circadian transcription (Sasaki et 2010). ARNTL:CLOCK and ARNTL2:CLOCK heterodimers powerfully activate the promoter of the gene coding for Plasminogen Activator Inhibitor (PAI)-1, officially called SERPINE1 and located on the seventh chromosome (7q21.3-q22), underlying the circadian variation in circulating PAI-1 (Hayashida et al, 2010;Maemura et al, 2000;Oishi, 2009;Oishi et al, 2009). ARNTL2:CLOCK, binding two E-box enhancers in the promoter, is twice more potent than ARNTL:CLOCK in its ability to activate SERPINE1 (Schoenhard et al, 2003), and in CD patients we have found up-regulation of the gene encoding PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…ARNTL2 may functionally replace ARNTL, and PER2 preferentially inhibits ARNTL2:CLOCK heterodimer activity, emphasizing its negative role and a positive role of ARNTL2 in the circadian transcription (Sasaki et 2010). ARNTL:CLOCK and ARNTL2:CLOCK heterodimers powerfully activate the promoter of the gene coding for Plasminogen Activator Inhibitor (PAI)-1, officially called SERPINE1 and located on the seventh chromosome (7q21.3-q22), underlying the circadian variation in circulating PAI-1 (Hayashida et al, 2010;Maemura et al, 2000;Oishi, 2009;Oishi et al, 2009). ARNTL2:CLOCK, binding two E-box enhancers in the promoter, is twice more potent than ARNTL:CLOCK in its ability to activate SERPINE1 (Schoenhard et al, 2003), and in CD patients we have found up-regulation of the gene encoding PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high preoperative plasma concentrations of PAI-1 are associated with shorter survival in patients with colorectal cancer (Nielsen et al 1998). Both CLOCK:ARNTL and CLOCK:ARNTL2 heterodimers powerfully activate the promoter of the PAI-1 gene, officially called SERPINE1 and located on the seventh chromosome (7q21.3-q22), underlying the circadian variation in circulating PAI-1 (Angleton et al 1989;Kurnik 1995;Maemura et al 2000;Oishi et al 2009;Oishi 2009;Hayashida et al 2010). CLOCK:ARNTL2, binding two E-box enhancers in the promoter, is much more potent than CLOCK:ARNTL in its ability to activate SERPINE1 (Schoenhard et al 2003;Sasaki et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…119,120 In murine WAT, mRNA expression of resistin and visfatin peaks during the dark phase, 16,120,122 while mRNA expression of PAI-1 is highest during the light phase. 114 Activity of plasma PAI-1, however, is highest at the beginning of the active phase. 114,123,124 TNFα peaks in serum of lean rats during the inactive phase.…”
Section: Adipokine Rhythmsmentioning
confidence: 99%
“…114 Activity of plasma PAI-1, however, is highest at the beginning of the active phase. 114,123,124 TNFα peaks in serum of lean rats during the inactive phase. 125,126 Interestingly, if mice are fed a HFD, the peak of serum TNFα shifts to the active phase.…”
Section: Adipokine Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation